Analisis Kompetensi Profesional Guru dalam Pemanfaatan TIK di Sekolah Dasar - Asmaarobiyah, Ratu; Hilaliyah, Tatu (Universitas PGRI Semarang, 2025)
Education is an effort that is planned to improve the quality of human resources so that they can compete. Teachers, as professional educators, have a very crucial role in achieving national education goals. This study aims to find out the extent of teachers' readiness to face these changes and how efforts to improve teacher competence can be carried out. This study uses a qualitative approach with a descriptive approach. Data collection instruments are in the form of observations, interviews and questionnaires. The data analysis procedures in this study are data reduction, data presentation, and conclusion drawn. The research site is SD Negeri Larangan, Jl. Waringin Kurung, Kampung Larangan, Harjatani Village, Kramatwatu District, Serang Regency, Banten Province. The determination of the sample of this study was using a simple random sampling technique. The results of the study show that most teachers use ICT devices in teaching and learning activities and master both in the management of administration and teaching materials, ICT applications applied in learning such as canva, educational games, whatsapp, youtube, learning houses, google classrooms, Kahoot, and even AI as well as strategic efforts in improving teachers' professional competence in the use of ICT.